2018
DOI: 10.1353/hpu.2018.0026
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Crime and Sexual Transmission Risk Behavior among Black Men Living with HIV

Abstract: Here, we examined the association of exposure to neighborhood crime with sexual risk-taking behavior among Black men living with HIV. HIV-positive Black men on anti-retroviral therapy in California completed an audio computer-assisted self-interview. Crime risk per census block group was derived from the Federal Bureau of Investigation’s Uniform Crime Report. Among 193 men, the mean (SD) number of sexual partners among those who were sexually active was 2.7 (3.3). 49% reported condomless sex, and 23% reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 56 publications
(52 reference statements)
0
9
0
Order By: Relevance
“…(47) Previous research also has found that exposure to community violence is associated with significantly higher rates of HIV-related transmission behaviors among YBMSM. (37,48,49) Importantly, poverty and incarceration are interlinked and independently associated with substance abuse and risk of HIV infection. (34,36,(50)(51)(52) Specifically, housing instability has been associated with justice system involvement (17) and HIV transmission among YBMSM.…”
Section: Syndemic Theorymentioning
confidence: 99%
“…(47) Previous research also has found that exposure to community violence is associated with significantly higher rates of HIV-related transmission behaviors among YBMSM. (37,48,49) Importantly, poverty and incarceration are interlinked and independently associated with substance abuse and risk of HIV infection. (34,36,(50)(51)(52) Specifically, housing instability has been associated with justice system involvement (17) and HIV transmission among YBMSM.…”
Section: Syndemic Theorymentioning
confidence: 99%
“…Adding these variables to analyses may help reduce the risk of bias due to measurement error in the AGS indices, this may be particularly useful for studies who aim to control for the confounding effects of crime. It is notable that the AGS index for total crime correlated only weakly with LAPD crime rates, but has been the most commonly used in health research (Tang et al, 2014, Ohri-Vachaspati et al, 2017, Lowe et al, 2016, Ojikutu et al, 2018, Broyles et al, 2016, Lowe et al, 2015, LAData, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…While to our knowledge, no publicly available research has validated the AGS CrimeRisk© indices, several studies have used the AGS crime indices in their research (Tang et al, 2014, Ohri-Vachaspati et al, 2017, Lowe et al, 2016, Ojikutu et al, 2018, Broyles et al, 2016, Lowe et al, 2015, LAData, 2010). These studies find effects in the expected direction and lend evidence to concordance validity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results showed that neighborhood insecurity formed a sizable portion of the largest cluster. Research has shown that neighborhood crime was associated with HIV risk taking behaviors such as unprotected sex and multiple sexual partnerships (11,12). Furthermore, a recent study observed that HIV-related mortality reached over 8% of released prison inmates in FG (13).…”
Section: Discussionmentioning
confidence: 99%